Expected Hierarchical Integration Reduces Perceptions of a Low Status Group as Less Competent than a High Status Group While Maintaining the Same Level of Perception of Warmth - Dang, Jianning; Liu, Li; Liang, Yuan; Ren, Deyun (Frontiers in Psychology, 2017)
The compensation effect, namely people’s tendency to judge one group more positively on some dimensions and the other group more positively on other dimensions, has been validated using real social categories and experimentally created groups. However, less attention has been paid to whether and how changes in social structure affect the emergence of the compensation effect. The present research first replicated the compensation effect using Chinese participants (Study 1). Then, two studies were conducted to examine the effects of group boundary permeability (Study 2) and the legitimacy of the social hierarchy (Study 3) on the emergence of the compensation effect. The results demonstrated that the compensation effect was more likely to emerge when the group boundary was impermeable and when the social hierarchy was legitimate. The implications of these findings and the effect of social change on intergroup perception are discussed.